Sensitivity of RegCM3 Simulated Precipitation over Southern Brazil with Different Boundary Conditions: ENSO Case - Simone Erotildes Teleginski Ferraz; Diego Pedroso (Advances in Meteorology, 2013)
This paper investigates the capability of a regional climate model (RegCM3) to simulate the Southern Brazil rainfall during three periods: the El Niño (1982), the neutral intermediary phase (1985), and the La Niña (1988). Each integration has used three of different boundary conditions available: NCEP-NCAR Reanalysis (I and II) and ECMWF Reanalysis—ERA-40. The simulations were performed covering a South America domain and some descriptive statistics analyses have been applied, like arithmetic mean, median, standard deviation and Pearson’s correlation; and frequencies histogram over Southern Brazil. The main results show that the model satisfactorily reproduces the rainfall in this region during the El Niño, neutral, and La Niña events, indicating that the boundary conditions which were tested adequately describe this simulations type.